A critical analysis of the practical man principle in Commissioner for Inland Revenue v Lever Brothers and Unilever Ltd - Grenville, David Paul (Rhodes University, Faculty of Commerce, Department of Accounting, 2014)
This research studies the practical person principle as it was introduced in the case of Commissioner for Inland Revenue v Lever Brothers and Unilever Ltd 1946 AD 441. In its time the Lever Brothers case was a seminal judgment in South Africa's tax jurisprudence and the practical person principle was a decisive criterion for the determination of source of income. The primary goal of this research was a critical analysis the practical man principle. This involved an analysis of the extent to which this principle requires judges to adopt a criterion that is too flexible for legitimate judicial decision-making. The extent to which the practical person principle creates a clash between a philosophical approach to law and an approach that is based on common sense or practicality was also debated. Finally, it was considered whether adopting a philosophical approach to determining the source of income could overcome the problems associated with the practical approach. A doctrinal methodology was applied to the documentary data consisting of the South African and Australian Income Tax Acts, South African and other case law, historical records and the writings of scholars. From the critical analysis of the practical person principle it was concluded that the anthropomorphised form of the principle gives rise to several problems that may be overcome by looking to the underlying operation of the principle. Further analysis of this operation, however, revealed deeper problems in that the principle undermines the doctrine of judicial precedent, legal certainty and the rule of law. Accordingly a practical approach to determining the source of income is undesirable and unconstitutional. Further research was conducted into the relative merits of a philosophical approach to determining source of income and it was argued that such an approach could provide a more desirable solution to determining source of income as well as approaching legal problems more generally.
Keywords: Unilever (Firm); South African Revenue Service; Taxation -- Law and legislation -- South Africa; Income tax -- Law and legislation -- South Africa -- Cases; Income tax -- South Africa -- Cases; Business enterprises -- Taxation -- South Africa; Law -- South Africa -- Philosophy